Methods of store construction / Muhammad Danish Imtiyaz Mat Radzi - Mat Radzi, Muhammad Danish Imtiyaz (Universiti Teknologi MARA, Perak, 2021)
Industry training is a mandatory requirement for students in certain programs at all levels of higher education at the Institution of Higher Education (IPT). Ipoh City Council is the place for industrial training to be conducted from 23 August 2021 to 7 January 2022. Students have been given the opportunity to undergo industrial training in the Management section. During the training period, students were taken to the construction site to see for themselves the work being done in conjunction with strengthening existing knowledge. In addition, disclosures can also add new knowledge. The performance and level of student skills will be evaluated by the supervisor responsible for the logbook.